THE ABIDING LEGACY OF THE REFORMATION’S CONFESSIONAL ORTHODOXY: THE REQUIRED VOWS OF WESTMINSTER SEMINARY PROFESSORS AND NAPARC MINISTERS - Lillback, Peter (Verbum Christi: Jurnal Teologi Reformed Injili, 2019)
This article revisits how Christians since almost two millenniums have made use of creeds and confessions. Especially confessional vows used at Westminster Theological Seminary, also refer to the vows of the churches who are members of NAPARC (The North American Presbyterian and Reformed Council). First, it examines the historical overview of various Reformed confessions, and historical survey of Reformed confessions from the Reformation to the present. Then, Westminster seminary's Presbyterian and Reformed heritage, and finally, authority of and subscription to the confessions. To define Reformed confessional theology which arose in the sixteenth and seventeenth century, this article include the table of the confessions of Westminster seminary or the NAPARC churches. KEYWORDS: creeds, confessions, Westminster, Reformed.